2018
DOI: 10.1159/000487404
|View full text |Cite
|
Sign up to set email alerts
|

Topical Treatment of Skin Injury Inflicted in Mice by X-Ray Irradiation

Abstract: Background/Aims: There is no treatment, without side effects, efficiently preventing or curing skin burns, caused by radiotherapy. A new experimental topical treatment protocol was assessed in mice receiving orthovoltage X-rays at an equivalent dose to that applied to human breast cancer patients in conventional radiotherapy. Methods: SKH-HR2 female hairless mice were irradiated on their dorsum with a total dose of 4,300 cGy during a 1-month period (20 fractions). The treatment group received a combination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 39 publications
2
21
0
Order By: Relevance
“…Wounds were induced on SKH-hr1 hairless male mice by surgically removing a 1 cm 2 piece of skin from the dorsal region of each mouse and were treated daily by topical application of ointments incorporating 1% of the five above-mentioned extracts, as well as an ointment containing 1% C. oestroides olive oil extract (COOE) previously investigated [21] for comparison purposes. Additionally, a group of mice receiving no topical treatment was used as negative control.…”
Section: Preparation Of Extracts and Evaluation Of Their Wound Healinmentioning
confidence: 99%
See 1 more Smart Citation
“…Wounds were induced on SKH-hr1 hairless male mice by surgically removing a 1 cm 2 piece of skin from the dorsal region of each mouse and were treated daily by topical application of ointments incorporating 1% of the five above-mentioned extracts, as well as an ointment containing 1% C. oestroides olive oil extract (COOE) previously investigated [21] for comparison purposes. Additionally, a group of mice receiving no topical treatment was used as negative control.…”
Section: Preparation Of Extracts and Evaluation Of Their Wound Healinmentioning
confidence: 99%
“…The marine isopod Ceratothoa oestroides is a parasite found in the buccal cavity of fish, causing serious lesions and often leading to the death of the host, especially of young fish [19,20]. Recently we have demonstrated the significant in vivo wound healing potential of a C. oestroides oily extract [21,22]. Herein, a series of different polarity (organic and aqueous) extracts of C. oestroides was prepared and evaluated for their wound healing activity on SKH-hr1 hairless mice, while the most active extract was fractionated for enrichment in the bioactive constituents.…”
Section: Introductionmentioning
confidence: 99%
“…Particular efforts have been made to address the negative effects of CS either on reducing or even eliminating the oxidative stress. In this context, Pinus halepensis bark extract has been used, which showed significant antioxidant and anti-inflammatory properties upon tobacco smoke, UV or X-rays irradiation of mouse skin, in vivo (27)(28)(29)37). Herein, our observations indicated that Pinus halepensis bark extract was able to protect primary mice keratinocytes from the effects of CS on both viability and oxidative stress, compared to other antioxidants or to the control (non treated) group.…”
Section: Discussionmentioning
confidence: 72%
“…On the other hand, there are many published studies, where the researchers evaluate the antioxidant activity of extracts of various plant extracts. Among them, Pinus halepensis, also known as Aleppo pine, is a Mediterranean pine with a bark extract rich in phenolic antioxidants, such as procyanidins and phenolic acids, which appears to effectively protect against skin inflammation induced by Xrays and UV radiation, in vivo (27,28). Moreover, Pinus maritima bark extract has been shown to protect skin against tobacco smoke and UV radiation (29)(30)(31).…”
mentioning
confidence: 99%
“…This result indicates that Zingerone inhibits the Ultraviolet B (UVB)-mediated production of pro-inflammatory cytokines, affects expression of cell cycle arrest and cell survival-related genes, attenuates UVB-induced cell damage. Meimeti et al suggested that gel containing Pinus halepensis bark aqueous extract and ointment containing olive oil extract of the marine isopod Ceratothoa oestroides mitigated skin injury induced by X-ray irradiation [ 113 ]. When 5% Pinus halepensis bark aqueous extract and 10% ointment containing olive oil extract of the marine isopod Ceratothoa oestroides were topically applied for 60 days, alleviation of skin redness and hydration was observed.…”
Section: Sequela Of Radiotherapy and Plant Extractsmentioning
confidence: 99%